Pengaruh Konsumsi Makanan Cepat Saji terhadap Status Gizi dan Aktivitas Fisik Pada Remaja: The Effect of Fast Food Consumption on Nutritional Status and Physical Activity Among Adolescents - Syah, M. Fahreza Miftahul; Murfat, Zulfitriani; Jafar, Muhammad Alfian; Safitri, Asrini; Safei, Imran (Chakra Brahmanda Lentera Institute, 2026)
The increasing consumption of fast food among adolescents has become an important public health concern due to its association with nutritional problems, particularly overweight and obesity. Fast food is generally high in calories, saturated fat, sugar, and sodium but low in essential nutrients. Combined with inadequate physical activity, these dietary habits may increase the risk of adverse health outcomes. This study aimed to analyze the effect of fast food consumption on nutritional status and physical activity among students. This analytical observational study employed a cross-sectional design. A total of 81 senior high school students were recruited using a total sampling technique. Fast food consumption was assessed using a Food Frequency Questionnaire (FFQ), physical activity was evaluated using a structured physical activity questionnaire, and nutritional status was determined based on Body Mass Index-for-Age (BMI-for-age). Data were analyzed using the Chi-square test with a significance level of 95% (α=0.05). The results showed that 81.5% of respondents had a low frequency of fast food consumption, while 18.5% frequently consumed fast food. Approximately 45.7% of respondents had normal nutritional status, whereas the remaining participants were classified as underweight, overweight, or obese. Bivariate analysis demonstrated a significant association between fast food consumption and nutritional status (p=0.000). However, no statistically significant association was found between fast food consumption and physical activity (p=0.438). In conclusion, fast food consumption significantly affects adolescents' nutritional status but is not significantly associated with their physical activity. Strengthening school-based nutrition education, promoting balanced dietary habits, and reducing fast food consumption are recommended to prevent nutritional problems among adolescents.